Kappa casein gen (CSN3) in horse: genetic variability in exon 1 and 4 - Sebastijan HOBOR; Tanja KUNEJ; Tina LENASI; Peter DOVČ (Acta Agriculturae Slovenica, 2006)
Kappa casein (κ-CN) is milk protein that determines the size and specific function of the casein micelles, and its clevage by chymosine is responsible for milk coagulation. Any variation in gene promoter or coding sequence may change the expression of the gene or amino acid sequence, effecting functional properties of the protein. The mature κ-CN is encoded by part of the exon 3 and the entire exon 4. Since exon 3 has 33 bp and exon 4 is 497 bp long, the major part of the protein is encoded by exon 4. In this study we identified two SNPs in exon 1 and two in exon 4 of the horse kappa casein gene (CSN3) and genotyped them in three horse breeds. The nucleotide sequence of the first exon was included in this study due to its possible role in the regulation of the CSN3 expression. Because these polymorphisms were analysed for the first time, we used a reference method (RFLP) or at least two other complementig methods (Bi-PASA/PIRA and ASA-PCR/PIRA), for molecular genetic analysis of above mentioned SNPs. The highest variation in genotype frequencies was present in Slovenian cold blood breed. SNPs in exon 4 cause amino acid (AA) change in the mature product, and may very well render chemical/functional properties of the protein. Analysis of the consequences caused by changes in AA sequence, by online avaible program tools, comfirmed our hypotesis.